Ferroelectric Phase Transition and Dielectric Response of Triglycine Sulphate Crystal and its Isomorphs - Upadhyay, T.C.; Sharma, Sandeep (Asian Journal of Chemistry, 2011)
Considering two sublattice pseudospin lattice coupled mode model of Chaudhuri et al. along with third and fourth-order phonon anharmonic interaction terms is considered for triglycine sulphate crystal and its isomorphs. With the help of double-time temperature dependent Green's function method, expressions for shift, width, soft mode frequency, dielectric constant and loss tangent are derived. By fitting model values in the theoretical expressions, temperature dependence of soft mode frequency, dielectric constant and loss tangent have been calculated. The theoretical results compare well with experimental results of Aravazhi et al.